Webinar Kesalahan Pola Asuh Orang Tua Yang Merusak Pertumbuhan Dan Perkembangan Anak Usia Dini - Maghfiroh, Shofia; Rahayu, Evi; Guswanti, Nelia; Seprya, Roby; Ramadhan, Syahri; Puspita, Yenda (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2023)
This article discusses the critical role of parents in forming the foundation for early childhood development through community service activities in the form of parenting webinars. The crucial phase of early childhood is the focus, where parents as leaders, mentors and supporters have the main responsibility. Although the process of educating children in this phase is not always smooth, attention to children's development in the family environment is very important. The article highlights the concept of parenting patterns and the impact of parenting errors, referring to the theories of Kohn and Baumrind. Parenting style is considered an important foundation for a child's character and well-being. Parenting webinars are presented as a response to modern challenges, using lecture, presentation, questionnaire and discussion methods. Despite technical challenges, webinars provide advantages in flexible access, interactivity, and durability of the material. The success of this webinar has made a positive contribution to the understanding of parents and early childhood educators regarding parenting mistakes. In conclusion, the role of parents in forming the foundation for early childhood development is the main focus, and parenting webinars are an effective means of achieving this goal. This service was held online by the Community Service and Development Institute (LPPM) STAI Al-Kifayah Riau, Early Childhood Islamic Education Study Program (PIAUD).